Extended Kalman Filter Based Linear Quadratic Regulator Control for Optical Wireless Communication Alignment - Asem Alalwan; Tadjine Mohamed; Messaoud Chakir; Taous Meriem Laleg (IEEE Photonics Journal, 2020)
High-precision positioning of two underwater mobile robots based on laser beams alignment has been investigated in this work. Usually, the control problem addressed in laser beams aims to maintain the position of the receiver robot aligned with the transmitter robot despite the effects of noise and active disturbances. In this paper, a new state space model is proposed. The latter is more precise than the usual used two state space model [1]. Furthermore, an estimation based control strategy using Extended Kalman Filter Estimator (EKF) and Linear Quadratic Regulator (LQR) is proposed to achieve the control objectives. LQR controller is well known as optimal control design with better tuning flexibility along with intrinsic robustness properties such as noise and output disturbance rejections. The achieved performance of the proposed controller is compared to the conventional proportional (P), Proportional-Integral-Derivative (PID) and Proportional-Integral (PI) controller to analyze the improvements and stability. In addition, an investigation of a sensitivity analysis is conducted to show robustness with different process noise variances of LQR controller.